2017
DOI: 10.1111/acer.13317
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Immune System Adaptations and Motivation for Alcohol in Non-Dependent Problem Drinkers

Abstract: Aims Increasing evidence suggests that levels of pro-inflammatory and anti-inflammatory cytokines are dysfunctional in alcohol dependence. Moreover, some initial findings demonstrate that these adaptations in peripheral inflammation may contribute to motivation for alcohol and problem drinking via possible direct effects or the indirect effects of stress responsivity. Importantly, the role of pro-inflammatory and anti-inflammatory cytokines in the progression from healthy to problem drinking is not well unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 58 publications
4
17
0
Order By: Relevance
“…Findings from our recent study of problem drinkers have additionally shown immune-suppression to predict craving, severity of problem use and alcohol consumption (Milivojevic in press). Marcos et al, (2008) also demonstrated a significant association between the −592C>A polymorphism of IL-10 and alcoholism, with an excess of allele A carriers being observed in alcohol dependent individuals (Crawley et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Findings from our recent study of problem drinkers have additionally shown immune-suppression to predict craving, severity of problem use and alcohol consumption (Milivojevic in press). Marcos et al, (2008) also demonstrated a significant association between the −592C>A polymorphism of IL-10 and alcoholism, with an excess of allele A carriers being observed in alcohol dependent individuals (Crawley et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-six problem drinkers and 38 social drinkers (see Table 2) - participated in a laboratory challenge procedure during which they were exposed to 3 personalized 5-minute imagery conditions (stress, relaxing, and alcohol cue, described in Section I), followed by the “alcohol taste test” (ATT) as a measure of implicit alcohol motivation and intake, presented across 3 consecutive days, 1 per day in a randomized and counterbalanced order (Milivojevic et al , 2017). Participants were characterized as problem or social drinkers according to Alcohol Use Disorder Identification Test (AUDIT) scores (>8 problem drinker, <8 social drinker).…”
Section: Binge-heavy Alcohol Alters Cortisol and Subjective Craving: mentioning
confidence: 99%
“…1). Context on each day was induced using our well-validated personalized guided imagery laboratory procedures which individually calibrate personal stressful events and have been shown to reliably provoke stress-induced and cue-induced craving in those with and without substance use disorders (Fox et al 2005; Fox et al 2007; Sinha et al 2007; Chaplin et al 2008; Sinha et al 2009; Sinha 2009b; Seo et al 2011; Fox et al 2010; Sinha et al, 2011a; Seo et al 2013; Milivojevic et al 2017). Finally, subjective craving and cortisol responses were also assessed post-ATT to examine both context and alcohol intake effects on these responses.…”
Section: Introductionmentioning
confidence: 99%